Animaux aquatiques et monstres des mers septentrionales : imaginer, connaître, exploiter, de l’Antiquité à 1600 ... : Aquatic Animals and Monsters of the Northern Seas Imagination, knowledge, exploitation, from Antiquity to 1600 ... - Calenda (OpenEdition, 2016)
Le colloque est consacré à l’histoire des poissons, monstres et mammifères aquatiques des mers septentrionales (Manche, mer du Nord, mer Baltique, Mer de Norvège, Atlantique Nord), de l'Antiquité à 1600. Trois thèmes vont structurer le colloque : savoirs et transmission (savoirs thérapeutiques, savoirs zoologiques, descriptions, identifications) savoir-faire et exploitations (élevage, pêche, cuisine, médecine) imaginaires et explorations. ... : The Colloquium is devoted to the history of fish, aquatic monsters and mammals in the northern seas (the English Channel, North Sea, Baltic Sea, Norwegian Sea, the North Atlantic), from antiquity to 1600. The colloquium is based on three themes: knowledge and the transmission of knowledge (medical knowledge, zoological knowledge, descriptions, identifications); savoir-faire and exploitation (aquatic farming, fishing, cooking, medicine); explorations – real and imaginary. ...